JASM: Active Pedagogy for Foreign Language Learning in Higher Education - Delplancq, Véronique (2020)
JASM project (Janela aberta sobre o mundo: línguas estrangeiras, criatividade multimodal e inovação pedagógica no ensino superior) consists of an experience of active pedagogy with students of the undergraduate course in Media Studies at the School of Education in Viseu (Portugal). The main objective of JASM is to promote the acquisition of multilingual and multicultural skills and to generate multilingual awareness. In addition to the cognitive dimension, students explore the aesthetic and emotional dimensions of language. Experiences of artistic creativity (media arts, multimedia art, among others) enable multimodal communication in English and French, starting off with information gathering pertaining to the cultural and linguistic diversity of Viseu. After conducting research on the countries of origin of the chosen nationalities as well as the underlying cultures, the students, working in groups, found out about the life stories of migrants on the basis of interviews. Experiences of artistic creativity made it possible to exercise multimodal communication. An object or a tradition mentioned in the stories told by migrants allowed them to build a fictional story around the said object or tradition. Photos were taken at all stages of this work. A storyboard of each fictional story was developed. The Korsakow system made it possible to create dynamic documentaries. The disclosure of this learning experience is made public on the project site and through an e-book.The students' language level (written and oral comprehension and expression) was assessed at the start of the project, using tests. The intermediate evaluation is of a qualitative type as well as the final evaluation (interview type, carried out with students and teachers) due to COVID-19 crisis. The progress of the learning process, as well as the involvement of the teachers could thus be documented.